Slurry composition, gas diffusion layer and preparation method thereof, and fuel cell

Through specific slurry compositions and stirring treatment techniques, a flat and uniform gas diffusion layer is prepared, which solves the problems of complex preparation processes and insufficient battery performance in the prior art, and significantly improves the output performance and durability of the fuel cell.

CN119297320APending Publication Date: 2025-01-10HUNAN JINBO HYDROGEN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411384904.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The preparation process of the existing proton exchange membrane fuel cell gas diffusion layer is complicated and complicated, which is not conducive to mass production and affects the output performance and durability of the battery.

Method used

Using a slurry composition of a specific mass ratio, including cellulose, dispersant, emulsifier, pore-forming agent and hydrophobic agent, a gas diffusion layer is prepared by stirring treatment and vacuum defoaming technology to form a flat and uniform microporous layer to enhance the battery output performance and durability.

Benefits of technology

The preparation process of the gas diffusion layer is simplified, and the output performance and durability of the fuel cell are significantly improved. Through uniform surface structure and pore size distribution, the current distribution is optimized, and local accumulation of moisture is prevented, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297320A_ABST
    Figure CN119297320A_ABST
Patent Text Reader

Abstract

The invention provides a slurry composition, a gas diffusion layer, a preparation method of the gas diffusion layer and a fuel cell, and the slurry composition is prepared from the following components in parts by mass: 0.1-2 parts of cellulose, 0.5-5 parts of a dispersing agent, 1-10 parts of an emulsifying agent, 1-10 parts of a pore forming agent, 60-80 parts of carbon powder and 15-40 parts of a water repellent agent. And the output performance and durability of the battery can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a slurry composition, in particular to a slurry composition, a gas diffusion layer and a preparation method thereof, and a fuel cell, belonging to the field of fuel cells. Background Art

[0002] Proton exchange membrane fuel cells are considered to be one of the most promising power generation technologies due to their high energy density, low-temperature start-up operation, pollution-free and zero-emission advantages. Proton exchange membrane fuel cells are composed of membrane electrodes, gas diffusion layers, bipolar plates, and end plates. During operation, hydrogen is introduced into the anode end to produce a hydrogen oxidation reaction, and oxygen is introduced into the cathode end to produce an oxygen reduction reaction. The product of the reaction is water. Among them, the gas diffusion layer is one of the core components of the proton exchange membrane fuel cell. It mainly plays the role of conducting electrons, transmitting hydrogen or air, and discharging water. It has an important impact on the output performance and durability of the proton exchange membrane fuel cell.

[0003] Patent application document CN106784883A provides a method for preparing a gas diffusion layer of a proton exchange membrane fuel cell. The preparation method comprises high-solid content slurry and low-solid content slurry, wherein the high-solid content slurry is scraped onto clean carbon paper, and then a layer of low-solid content slurry is sprayed, and finally sintered to form a flat, crack-free, low-carbon-loaded microporous layer to obtain a gas diffusion layer. However, the process is cumbersome and complicated, which is not conducive to mass production.

[0004] Therefore, exploring technical solutions with simple processes and improved battery output performance and durability has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0005] The invention provides a slurry composition, which can significantly improve the output performance and durability of a battery after being used to prepare a gas diffusion layer.

[0006] The present invention also provides a gas diffusion layer, which can significantly improve the output performance and durability of a battery after being used in the battery.

[0007] The present invention also provides a method for preparing a gas diffusion layer. The preparation method has a simple process, and the prepared gas diffusion layer can be used in a battery to significantly improve the output performance and durability of the battery.

[0008] The present invention also provides a fuel cell, which includes the gas diffusion layer and has excellent output performance and durability.

[0009] On one hand, the present invention provides a slurry composition, which comprises, by weight, 0.1-2 parts of cellulose, 0.5-5 parts of dispersant, 1-10 parts of emulsifier, 1-10 parts of pore former, 60-80 parts of carbon powder, and 15-40 parts of hydrophobic agent.

[0010] The slurry composition as described above comprises, by weight, 0.5-1.5 parts of cellulose, 1-3 parts of dispersant, 3-8 parts of emulsifier, 2-8 parts of pore former, 65-75 parts of carbon powder, and 25-35 parts of hydrophobic agent.

[0011] The slurry composition as described above further comprises an alcohol aqueous solution, wherein the volume ratio of the alcohol compound to water in the alcohol aqueous solution is 1:(0.1-1).

[0012] In the slurry composition as described above, the alcohol compound includes at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol and n-pentanol.

[0013] In the slurry composition as described above, the mass average molecular weight of the cellulose is 600,000 to 1,000,000.

[0014] The slurry composition as described above, wherein the cellulose comprises at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and sodium hydroxymethyl cellulose;

[0015] And / or, the dispersant includes at least one of sodium stearate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate;

[0016] And / or, the emulsifier includes at least one of Tween 80, polysorbate 60, polyoxyethylene cetyl alcohol, and Triton;

[0017] And / or, the pore-forming agent includes at least one of ammonium carbonate, ammonium oxalate, ammonium bicarbonate, and ammonium chloride;

[0018] and / or, the carbon powder comprises at least one of XC-72, XC-72R, Ketjen black, carbon nanotubes, graphene, graphite, and nano-carbon fibers;

[0019] And / or, the hydrophobic agent includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer.

[0020] In another aspect, the present invention provides a gas diffusion layer, comprising a carbon paper base layer and a microporous layer covering at least one surface of the carbon paper base layer; the microporous layer comprises the slurry composition as described above; and the roughness of the microporous layer does not exceed 2.5 microns.

[0021] In the gas diffusion layer as described above, the average pore size of the microporous layer is 100-300 nm.

[0022] In another aspect, the present invention provides a method for preparing the gas diffusion layer as described above, comprising the following steps:

[0023] 1) subjecting a slurry composition including an alcohol aqueous solution to a first stirring treatment to obtain a dispersed mixed slurry;

[0024] 2) subjecting the dispersed mixed slurry to a second stirring treatment under a vacuum degree of 0.05-0.1 MPa, wherein the rotation speed of the second stirring treatment is 500-2000 rpm and the time is 5-30 min, and then coating the mixed slurry on the surface of the carbon paper substrate, drying and sintering to obtain a gas diffusion layer.

[0025] In another aspect, the present invention provides a fuel cell, comprising the gas diffusion layer as described above or the gas diffusion layer prepared by the preparation method as described above.

[0026] The slurry composition provided by the present invention includes specific mass parts of cellulose, dispersant, emulsifier, pore former, carbon powder and hydrophobic agent. Under the synergistic effect of various components, the gas diffusion layer prepared for fuel cell can significantly improve the output performance and durability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a picture of the mixed slurry after the second stirring treatment provided in Example 1 of the present invention;

[0028] Figure 2 This is a picture of the mixed slurry after the second stirring treatment provided in Comparative Example 3 of the present invention;

[0029] Figure 3 An optical electron microscope photograph of a gas diffusion layer provided in Example 1 of the present invention;

[0030] Figure 4 This is an optical electron microscope photograph of the gas diffusion layer provided for Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] On one hand, the present invention provides a slurry composition, which comprises, by weight, 0.1-2 parts of cellulose, 0.5-5 parts of dispersant, 1-10 parts of emulsifier, 1-10 parts of pore former, 60-80 parts of carbon powder, and 15-40 parts of hydrophobic agent.

[0033] The slurry composition provided by the invention is used for preparing a gas diffusion layer of a fuel cell.

[0034] The gas diffusion layer prepared by the slurry composition has good flatness and uniformity. When the gas diffusion layer is used in a battery, the battery has excellent output performance and durability. The inventor analyzed this and believed that the reason may be that: under the synergistic effect of various components in specific mass parts, the leveling and uniformity of the slurry can be improved, the microcracks of the coating can be effectively reduced, and the surface of the gas diffusion layer can be uniform and flat. The uniform surface structure is conducive to the uniform distribution and effective removal of moisture, preventing the local accumulation of moisture in the battery, causing the gas transmission to be blocked, and helping to improve the output performance of the fuel cell; at the same time, it can provide uniform current distribution on the electrode, avoid the problem of excessively high or low local current density, and thus optimize the durability of the battery.

[0035] Furthermore, in a specific embodiment of the present invention, the composition comprises, by weight, 0.5-1.5 parts of cellulose, 1-3 parts of dispersant, 3-8 parts of emulsifier, 2-8 parts of pore former, 65-75 parts of carbon powder, and 25-35 parts of hydrophobic agent.

[0036] Specifically, the mass fraction of cellulose includes but is not limited to 0.5, 0.8, 1.0, 1.2, 1.4, 1.5 or any range between two of them; the mass fraction of dispersant includes but is not limited to 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3 or any range between two of them; the mass fraction of emulsifier includes but is not limited to 3, 4, 5, 6, 7, 8 or any range between two of them; the mass fraction of pore-forming agent includes but is not limited to 3, 4, 5, 6, 7, 8 or any range between two of them; The mass parts of include but are not limited to 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or the range between any two of them, the mass parts of carbon powder include but are not limited to 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts or the range between any two of them, the mass parts of hydrophobic agent include but are not limited to 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts or the range between any two of them.

[0037] When the mass fractions of various substances in the slurry composition meet the above ranges, the prepared gas diffusion layer is more flat and uniform, and the battery has more excellent output performance and durability after being used in the battery.

[0038] Furthermore, in a specific embodiment of the present invention, the slurry composition also includes an alcohol aqueous solution, and the volume ratio of the alcohol compound to water in the alcohol aqueous solution is 1: (0.1-1).

[0039] Specifically, the alcohol aqueous solution refers to a solvent composed of an alcohol compound and ultrapure water.

[0040] The volume ratio of the alcohol compound to water includes but is not limited to 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1 or any range therebetween.

[0041] When the slurry composition includes an alcohol aqueous solution prepared according to the above volume ratio, it can not only improve the fluidity of the slurry composition and enhance the dispersibility, but also adjust the slurry composition within a suitable viscosity range to ensure subsequent performance.

[0042] Furthermore, in a specific embodiment of the present invention, the alcohol compound includes at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol, and n-pentanol.

[0043] The above-mentioned alcohol compounds can optimize the performance of the slurry composition and improve the dispersibility.

[0044] Furthermore, in a specific embodiment of the present invention, the mass average molecular weight of cellulose is 600,000-1,000,000.

[0045] Specifically, the mass average molecular weight of cellulose includes, but is not limited to, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000, 1,000,000, or a range between any two of these.

[0046] The present invention does not limit the specific source of cellulose, and cellulose meeting the above mass average molecular weight can be obtained through commercial channels.

[0047] The mass average molecular weight of cellulose can be detected by common methods in the art, such as mass spectrometry, gel permeation chromatography, and the like.

[0048] The molecular weight of cellulose ranges from several thousand to several million. Through experimental verification, it is found that the best effect is to use cellulose with a molecular weight of 600,000 to 1 million as a leveling agent for the microporous layer slurry. The main reason is that the molecular weight of cellulose within this range is large, and its aqueous solution viscosity is relatively large, which has a significant effect on adjusting the viscosity, thixotropy and other leveling properties of the slurry. After a small amount of addition, it can improve the flatness and reduce cracks. At the same time, due to the small amount of addition, the negative effect of cellulose on the pore structure of the microporous layer can be almost ignored.

[0049] Further, in a specific embodiment of the present invention, the cellulose includes at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and sodium hydroxymethyl cellulose; and / or the dispersant includes at least one of sodium stearate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate; and / or the emulsifier includes at least one of Tween 80, polysorbate 60, polyoxyethylene cetyl alcohol, and Triton; and / or the pore-forming agent includes at least one of ammonium carbonate, ammonium oxalate, ammonium bicarbonate, and ammonium chloride; and / or the carbon powder includes at least one of XC-72, XC-72R, Ketjen black, carbon nanotubes, graphene, graphite, and nano-carbon fibers; and / or the hydrophobic agent includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer.

[0050] In another aspect, the present invention provides a gas diffusion layer, comprising a carbon paper substrate and a microporous layer covering at least one surface of the carbon paper substrate; the microporous layer comprises the slurry composition as described above; and the roughness of the microporous layer does not exceed 2.5 microns.

[0051] The gas diffusion layer may be composed of a carbon paper base layer and a microporous layer covering one surface of the carbon paper base layer, or the gas diffusion layer may be composed of a carbon paper base layer and microporous layers covering both surfaces of the carbon paper base layer.

[0052] The microporous layer has some tiny protrusions or depressions, wherein the maximum distance between the protrusions of the microporous layer and the plane where the microporous layer surface is located does not exceed 2.5 microns, and the maximum distance between the depressions of the microporous layer and the plane where the microporous layer surface is located does not exceed 2.5 microns.

[0053] The roughness of the microporous layer can be tested using common testing methods in the art, such as laser scanning microscopy, atomic force microscopy, and the like.

[0054] The gas diffusion layer provided by the present invention can significantly improve the output performance and durability of the battery after being used in the battery. The inventors have analyzed this and believe that the reason may be that, on the one hand, under the synergistic effect of the various components of the slurry composition, the microporous layer has fewer cracks and relatively excellent flatness. On the other hand, the roughness of the microporous layer does not exceed 2.5 microns, which also means that the microporous layer has excellent flatness, thereby enabling the gas diffusion layer to have excellent output performance and durability when used in the battery.

[0055] Furthermore, the average pore size of the microporous layer is 100-300 nm.

[0056] The surface of the microporous layer has a certain number of pores, and the average pore size of the microporous layer can be measured by scanning electron microscopy, transmission electron microscopy, nitrogen adsorption-desorption analysis, image analysis and the like.

[0057] In detail, the average pore size of the microporous layer includes but is not limited to 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm or a range between any two thereof.

[0058] When the average pore size of the microporous layer is within the above range, the reaction gas can be distributed more evenly, the gas penetration resistance can be reduced, and the conductivity can be improved to ensure the output performance and durability of the battery.

[0059] In another aspect, the present invention provides a method for preparing the gas diffusion layer as described above, comprising the following steps:

[0060] 1) subjecting a slurry composition including an alcohol aqueous solution to a first stirring treatment to obtain a dispersed mixed slurry;

[0061] 2) The dispersed mixed slurry is subjected to a second stirring treatment under a vacuum degree of 0.05-0.1 MPa, the rotation speed of the second stirring treatment is 500-2000 rpm, and the time is 5-30 min. Subsequently, the mixed slurry is coated on the surface of the carbon paper substrate, dried and sintered to obtain a gas diffusion layer.

[0062] Specifically, in step 1), the slurry mixture including the alcohol aqueous solution is subjected to a first stirring treatment to uniformly mix the various components in the slurry mixture to obtain a dispersed mixed slurry.

[0063] In a specific embodiment, the first stirring treatment is performed at a rotation speed of 3000-10000 rpm and for a time of 30-120 min.

[0064] It can be understood that in order to reduce the load of the first stirring treatment and improve the uniformity of the various components of the mixed slurry, the slurry mixture including the alcohol aqueous solution can be prepared by adding in steps.

[0065] In a specific embodiment, an alcohol compound is mixed with ultrapure water to obtain an alcohol aqueous solution, and then a dispersant, cellulose, an emulsifier, and a pore-forming agent are added to the alcohol aqueous solution in sequence to obtain a mother liquor, and carbon powder and a hydrophobic agent are added to the mother liquor to obtain a slurry mixture including the alcohol aqueous solution.

[0066] In step 2), the dispersed mixed slurry is added to a vacuum stirring degassing device, the vacuum degree is adjusted to 0.05-0.1 MPa, and a second stirring treatment is performed at 500-2000 rpm for 5-30 min to obtain a degassed mixed slurry, which is coated on the surface of the carbon paper base layer and dried and sintered to obtain a gas diffusion layer.

[0067] In detail, the vacuum degree of the second stirring treatment includes but is not limited to 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa, 0.09MPa, 0.1MPa or any range between two thereof. The rotation speed of the second stirring treatment includes but is not limited to 500, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000 or any range between two thereof. The treatment time includes but is not limited to 5min, 10min, 15min, 20min, 25min, 30min or any range between two thereof.

[0068] The second stirring treatment is carried out under vacuum to effectively eliminate bubbles in the mixed slurry, laying a foundation for the subsequent preparation of a microporous layer with high flatness.

[0069] The present invention does not limit the specific method of the drying and sintering treatment, and the drying and sintering treatment can be carried out in a common manner in the art.

[0070] In a specific embodiment, the drying and sintering process is performed at a temperature of 360° C. to 400° C. and for a time of 30 to 120 minutes.

[0071] The preparation method of the gas diffusion layer provided by the present invention can significantly improve the output performance and durability of the battery after the prepared gas diffusion layer is used in the battery. On the one hand, a slurry mixture of specific components is used as a raw material, and the uniformity of the slurry mixture is improved under the coordinated cooperation of each component, thereby improving the output performance and durability of the battery; on the other hand, after the first stirring treatment and the second stirring treatment, the tiny bubbles in the mixed slurry are effectively eliminated, and the bubbles are prevented from causing uneven distribution of the subsequent slurry, further improving the uniformity of the subsequent microporous layer, thereby improving the output performance and durability of the battery.

[0072] In another aspect, the present invention provides a fuel cell, comprising the gas diffusion layer as described above or the gas diffusion layer prepared by the preparation method as described above.

[0073] The fuel cell provided by the present invention includes the above-mentioned gas diffusion layer, and thus has excellent output performance and durability.

[0074] It can be understood that the fuel cell provided by the present invention includes five major parts: a single cell, an air supply system, a hydrogen supply system, a water heat management system and a load system.

[0075] Among them, the stack is the core component of the fuel cell system, maintaining the energy output process of the entire fuel cell system, and largely determines the key factors such as the overall performance, life and cost of the fuel cell. The stack is mainly composed of a single fuel cell, and the common stack structure includes end plates, current collectors, bipolar plates, and membrane electrodes. The membrane electrode includes a gas diffusion layer, a catalyst layer, and a proton exchange membrane. The gas diffusion layer is located between the catalyst electrode and the bipolar plate, and plays an important role in supporting the catalyst layer, collecting current, conducting gas, and discharging the reaction product water.

[0076] Hereinafter, the slurry composition and the gas diffusion layer provided by the present invention are described in detail through specific examples.

[0077] Example 1

[0078] The slurry composition provided in this embodiment includes 1.4g carboxymethyl cellulose (mass average molecular weight is 800,000), 2.8g sodium dodecylbenzene sulfonate, 7g Tween 80, 6.5g ammonium bicarbonate, 100g Cabot carbon black XC-72, 40g polytetrafluoroethylene, and 1200mL alcohol aqueous solution, wherein the volume ratio of ethanol to water in the alcohol aqueous solution is 1:0.5.

[0079] The method for preparing the gas diffusion layer provided in this embodiment comprises the following steps:

[0080] 1. Measure 800 mL of ultrapure water and 400 mL of ethanol to prepare a mixed solvent, then add 1.4 g of cellulose carboxymethyl cellulose, 2.8 g of dispersant sodium dodecylbenzene sulfonate, 7 g of emulsifier Tween 80, and 6.5 g of pore-forming agent ammonium bicarbonate to the mixed solvent in sequence. The mother liquor can be obtained after simple mechanical stirring; select Cabot Carbon Black XC-72 as the conductive carbon black, weigh 100 g and add it to the slurry mother liquor, select polytetrafluoroethylene as the hydrophobic agent, weigh 40 g of polytetrafluoroethylene and add it to the mother liquor to obtain a slurry composition including an alcohol aqueous solution, add the slurry composition including an alcohol aqueous solution to a shearing machine and perform the first stirring treatment at 5000 rpm, the dispersion time is 60 min, and a dispersed mixed slurry is obtained.

[0081] 2. Add the dispersed mixed slurry into the vacuum degassing equipment, turn on the vacuum, set the vacuum degree to 0.08MPa, and after reaching the vacuum degree, carry out the second stirring treatment, set the rotation speed to 1500rpm, and the treatment time to 20min to obtain the degassed mixed slurry. After coating and high-temperature sintering, the gas diffusion layer is obtained.

[0082] After testing, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 1.2 μm, and the average pore size is 206 nm. Figure 1This is a picture of the deaerated mixed slurry of this embodiment. It can be seen that the deaerated mixed slurry obtained after the second stirring treatment of this embodiment has good uniformity. Figure 3 The optical electron microscope image of the gas diffusion layer provided in this embodiment shows that the microporous layer of the gas diffusion layer provided in this embodiment is flat and has no cracks.

[0083] Example 2

[0084] The slurry composition provided in this embodiment includes 0.7g hydroxyethyl cellulose (mass average molecular weight is 600,000), 1.4g sodium stearate, 4.5g Triton, 3g ammonium oxalate, 100g Ketjen black, 35g polyvinylidene fluoride, and 1500mL alcohol aqueous solution, wherein the volume ratio of methanol to water in the alcohol aqueous solution is 1:0.1.

[0085] The method for preparing the gas diffusion layer provided in this embodiment comprises the following steps:

[0086] 1. Measure 136 mL of ultrapure water and 1364 mL of methanol to prepare a mixed solvent, and then add 0.7 g of hydroxyethyl cellulose, 1.4 g of sodium stearate, 4.5 g of Triton, and 3 g of ammonium oxalate to the mixed solvent in sequence. The mother liquor can be obtained after simple mechanical stirring; Ketjen black is selected as the carbon powder, 100 g is weighed and added to the slurry mother liquor, polyvinylidene fluoride is selected as the hydrophobic agent, 35 g of polyvinylidene fluoride is weighed and added to the mother liquor to obtain a slurry composition including an alcohol aqueous solution, and the slurry composition including an alcohol aqueous solution is added to a shearing machine for the first stirring treatment at 3000 rpm, and the dispersion time is 120 min to obtain a dispersed mixed slurry.

[0087] 2. Add the dispersed mixed slurry into the vacuum degassing equipment, turn on the vacuum, set the vacuum degree to 0.1MPa, and after reaching the vacuum degree, carry out the second stirring treatment, set the speed to 500rpm, and the treatment time to 30min. The obtained slurry is coated and sintered at high temperature to obtain a gas diffusion layer.

[0088] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 1.5 μm, and the average pore diameter is 231 nm.

[0089] Example 3

[0090] The slurry composition provided in this embodiment includes 2.3g hydroxypropyl methylcellulose (mass average molecular weight is 1 million), 4.5g sodium fatty alcohol ether sulfate, 12g polysorbate 60, 12g ammonium chloride, 100g carbon nanotubes, 50g fluorinated ethylene propylene copolymer, and 1600mL alcohol aqueous solution, wherein the volume ratio of n-propanol to water in the alcohol aqueous solution is 1:1.

[0091] The method for preparing the gas diffusion layer provided in this embodiment comprises the following steps:

[0092] 1. 800 mL of ultrapure water and 800 mL of n-propanol were measured to prepare a mixed solvent, and then 2.3 g of hydroxypropyl methylcellulose, 4.5 g of sodium fatty alcohol ether sulfate, 12 g of polysorbate 60, and 12 g of ammonium chloride were added to the mixed solvent in sequence, and a mother liquor was obtained after simple mechanical stirring; 100 g of carbon nanotubes were weighed and added to the slurry mother liquor, and 60 g of fluorinated ethylene propylene copolymer was weighed and added to the mother liquor to obtain a slurry composition including an alcohol aqueous solution, and the slurry composition including an alcohol aqueous solution was added to a shearing machine and subjected to a first stirring treatment at 10,000 rpm for a dispersion time of 30 min to obtain a dispersed mixed slurry.

[0093] 2. Add the dispersed mixed slurry into the vacuum degassing equipment, turn on the vacuum, set the vacuum degree to 0.05MPa, and after reaching the vacuum degree, carry out the second stirring treatment, set the speed to 2000rpm, and the treatment time to 5min. The obtained slurry is coated and sintered at high temperature to obtain a gas diffusion layer.

[0094] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 1 μm, and the average pore size is 140 nm.

[0095] Example 4

[0096] The slurry composition provided in this embodiment includes 0.3g carboxymethyl cellulose (mass average molecular weight is 700,000), 6.3g sodium dodecylbenzene sulfonate, 1.3g Tween 80, 1.3g ammonium bicarbonate, 100g Cabot carbon black XC-72, 25g polytetrafluoroethylene, and 1200mL alcohol aqueous solution, wherein the volume ratio of ethanol to water in the alcohol aqueous solution is 1:0.5.

[0097] The preparation method of the gas diffusion layer provided in this embodiment is basically the same as that in Example 1, except that in step 1), the carboxymethyl cellulose is 0.3 g, the sodium dodecylbenzene sulfonate is 6.3 g, the Tween 80 is 1.3 g, the ammonium bicarbonate is 1.3 g, the Cabot carbon black XC-72 is 100 g, and the polytetrafluoroethylene is 25 g.

[0098] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 1.7 μm, and the average pore diameter is 241 nm.

[0099] Example 5

[0100] The slurry composition provided in this embodiment is basically the same as that in Embodiment 1, except that the mass average molecular weight of the carboxymethyl cellulose is 500,000.

[0101] The preparation method of the gas diffusion layer provided in this embodiment is basically the same as that in embodiment 1, except that in step 1), the mass average molecular weight of the carboxymethyl cellulose is 500,000.

[0102] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 3 μm, and the average pore diameter is 162 nm.

[0103] Example 6

[0104] The slurry composition provided in this embodiment is basically the same as that in Embodiment 1, except that the volume ratio of ethanol to water in the alcohol aqueous solution is 1:1.18.

[0105] The preparation method of the gas diffusion layer provided in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the volume of ethanol is 550 mL, and the volume of ultrapure water is 650 mL.

[0106] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 3.2 μm, and the average pore size is 120 nm.

[0107] Example 7

[0108] The slurry composition provided in this embodiment is consistent with that in Example 1.

[0109] The preparation method of the gas diffusion layer provided in this embodiment is basically the same as that in Embodiment 1, except that 80 g of polytetrafluoroene is added.

[0110] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this embodiment is 1.3 μm, and the average pore size is 50 nm.

[0111] Comparative Example 1

[0112] The slurry composition provided in this comparative example is substantially the same as that in Example 1, except that carboxymethyl cellulose is not included.

[0113] The preparation method of the gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that:

[0114] In step 1), no carboxymethyl cellulose is added.

[0115] After testing, the roughness of the microporous layer in the gas diffusion layer provided in this comparative example is 5.2 μm. Figure 4 The optical electron microscope image of the gas diffusion layer provided in this comparative example shows that the microporous layer of the gas diffusion layer provided in this comparative example has many cracks and poor flatness.

[0116] Comparative Example 2

[0117] The slurry composition provided in this comparative example is substantially the same as that in Example 1, except that the mass of the carboxymethyl cellulose is 0.1 g.

[0118] The preparation method of the gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that:

[0119] In step 1), the mass of carboxymethyl cellulose is 0.1 g.

[0120] According to the test, the roughness of the microporous layer in the gas diffusion layer provided in this comparative example is 4.1 μm.

[0121] Comparative Example 3

[0122] The slurry composition provided in this comparative example is consistent with that in Example 1.

[0123] The preparation method of the gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that:

[0124] 2. The dispersed mixed slurry is subjected to a second stirring treatment, the rotation speed is set to 1500 rpm, and the treatment time is 20 minutes. The obtained mixed slurry is coated and sintered at high temperature to obtain a gas diffusion layer.

[0125] After testing, the roughness of the microporous layer in the gas diffusion layer provided in this comparative example is 4.5 μm. Figure 2 The picture of the slurry obtained by the second stirring treatment provided in this comparative example shows that obvious bubbles exist in the slurry.

[0126] Test Case

[0127] The gas diffusion layers provided in all the embodiments and comparative examples were assembled into a proton exchange membrane fuel cell for testing.

[0128] Among them, the effective area of ​​the membrane electrode is 5×5cm 2 The platinum loading of the anode and cathode catalyst layers is 0.4 mg / cm 2 DuPont Nafion211 membrane was selected as the proton membrane. The battery operating temperature was 80°C, the anode and cathode hydrogen and air intakes were set to a stoichiometric ratio of 1.2 and 2.5 respectively, and the intake humidity was 80% RH.

[0129] The anode hydrogen deficiency experiment was used to evaluate the durability of the gas diffusion layer. During the test, nitrogen was introduced into the anode and air was introduced into the cathode. The current density was set to 300 mA / cm 2 , the cut-off voltage is -1.5V. The durability of the gas diffusion layer is evaluated by comparing the voltage drop before and after the hydrogen deficiency experiment. The specific test results are shown in Table 1.

[0130] Table 1

[0131]

[0132] It can be seen from Table 1 that Comparative Example 3 was not deaerated, the microporous layer slurry had obvious bubbles, the coating was unevenly coated, and the initial output performance and durability were not as good as those of Examples 1-7 that were deaerated; Comparative Example 1 did not add cellulose, the initial performance was poor, and the attenuation before and after the hydrogen deficiency experiment was 97mV, indicating that in order to improve the durability, cellulose must be added to improve the coating flatness; Comparative Example 2 is a sample with a small amount of cellulose added. The initial performance and durability of this sample are somewhat different from those of Example 1, indicating that there is an optimal range for the amount of cellulose added.

[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A slurry composition, characterized in that: The composition comprises, by weight, 0.1-2 parts of cellulose, 0.5-5 parts of dispersant, 1-10 parts of emulsifier, 1-10 parts of pore former, 60-80 parts of carbon powder and 15-40 parts of hydrophobic agent.

2. The slurry composition according to claim 1, characterized in that The composition comprises, by weight, 0.5-1.5 parts of cellulose, 1-3 parts of dispersant, 3-8 parts of emulsifier, 2-8 parts of pore-forming agent, 65-75 parts of carbon powder, and 25-35 parts of hydrophobic agent.

3. The slurry composition according to claim 1 or 2, characterized in that: It also includes an alcohol aqueous solution, in which the volume ratio of alcohol compounds to water is 1:(0.1-1).

4. The slurry composition according to claim 3, characterized in that The alcohol compound includes at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol and n-pentanol.

5. The slurry composition according to any one of claims 1 to 4, characterized in that: The mass average molecular weight of the cellulose is 600,000-1,000,000.

6. The slurry composition according to any one of claims 1 to 5, characterized in that: The cellulose includes at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and sodium hydroxymethyl cellulose; And / or, the dispersant includes at least one of sodium stearate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate; And / or, the emulsifier includes at least one of Tween 80, polysorbate 60, polyoxyethylene cetyl alcohol, and Triton; And / or, the pore-forming agent includes at least one of ammonium carbonate, ammonium oxalate, ammonium bicarbonate, and ammonium chloride; and / or, the carbon powder comprises at least one of XC-72, XC-72R, Ketjen black, carbon nanotubes, graphene, graphite, and nano-carbon fibers; And / or, the hydrophobic agent includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer.

7. A gas diffusion layer, characterized in that: It comprises a carbon paper base layer and a microporous layer covering at least one surface of the carbon paper base layer; the microporous layer comprises the slurry composition according to claim 1 or 2; and the roughness of the microporous layer does not exceed 2.5 microns.

8. The gas diffusion layer according to claim 7, characterized in that: The average pore size of the microporous layer is 100-300 nm.

9. A method for preparing a gas diffusion layer according to claim 7 or 8, characterized in that: The following steps are involved: 1) subjecting a slurry composition including an alcohol aqueous solution to a first stirring treatment to obtain a dispersed mixed slurry; 2) subjecting the dispersed mixed slurry to a second stirring treatment under a vacuum degree of 0.05-0.1 MPa, wherein the rotation speed of the second stirring treatment is 500-2000 rpm and the time is 5-30 min, and then coating the mixed slurry on the surface of the carbon paper substrate, drying and sintering to obtain a gas diffusion layer.

10. A fuel cell, characterized in that: The invention comprises the gas diffusion layer according to claim 7 or 8 or the gas diffusion layer prepared by the preparation method according to claim 9.

Citation Information

Patent Citations

  • Preparation method of flat crack-free low-carbon load microporous layer of proton exchange membrane fuel cell

    CN106784883A